The influences of New School Movement in the conception of pedagogical manuals of the language area - Cardoso Moura, Marco Aurélio; Nonato Gomes Santos, Sandoval (Universidade Estadual de Campinas, 2020)
This study proposes to discuss the role that New School Movement plays in the development of teacher training manuals for the language area, specifically through the analysis of the manual Language Methodology, by Orlando Leal Carneiro, published in 1959. To achieve this, the study initially proceeds with an analysis of experimental psychology postulates synthesized by Jean Piaget. Then, it recovers the New School Movement historical link with experimental psychology in Brazil. Finally, it focuses on the manual, through documental research and textual analysis, seeking to understand a dimension of the teacher training history in Brazil and its relation with the New School Movement.